Implementation of the Role of Computer Networks in the Digital Era - Sulastri Eksan; Hana Salindeho; Engelica Ruring; Nazla Israel; Tiara Manoy (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Background: The digital era has profoundly transformed human interaction, communication, and information management across virtually all sectors of society. These changes are closely linked to the role of computer networks, which serve as the foundational infrastructure enabling rapid, secure, and integrated data exchange. The exponential growth of internet-connected devices, cloud computing services, and real-time communication platforms has placed computer networks at the center of contemporary digital civilization. Objective: This literature review analyzes the implementation of computer networks across various sectors by examining scientific publications, research reports, and institutional data, with the aim of identifying their strategic roles, contributions, and ongoing challenges in supporting digital transformation. Methods: A literature review methodology was employed by gathering and systematically analyzing relevant sources including peer-reviewed journals, books, government reports, and institutional publications. The approach focused on synthesizing existing knowledge across multiple sectors to provide a comprehensive understanding of computer networks' evolving role in the digital era. Results: The findings demonstrate that computer networks play strategic roles in global communication, digital education, technology-driven economies, modern governance, industrial automation and IoT, cybersecurity, and international collaboration. Computer networks function not merely as technical tools but as strategic pillars supporting the development of an inclusive and sustainable digital ecosystem. Conclusion: Computer networks are essential to global digital transformation. Optimizing their use requires robust infrastructure development, adaptive regulatory frameworks, improved digital literacy, and multi-stakeholder collaboration to ensure equitable and sustainable network access across all societal sectors.